Antioxidant and Elastase Inhibitor Potential of Petals and Receptacle of Rose Flower (Rosa damascena) - Evi Mawarni; Chrismis Novalinda Ginting; Linda Chiuman; Ermi Girsang; Rr. Anisa Siwianti Handayani; Wahyu Widowati (Universitas Indonesia, 2020)
Free radicals can cause damage to cells or tissues, autoimmune diseases, degenerative diseases, or cancer. Therefore, the body needs important substances, namely antioxidants that can help protect the body by reducing negative effect from free radicals. Rose flower (Rosa damascena) has anthocyanin pigment which belongs to flavonoid group which has a function as antioxidant or free radical scavenger. This study aims to determine antioxidant and anti-elastase potentials of rose petals and receptacles. The method used in this study was a qualitative phytochemical test to determine the compounds contained in the Rose Petal Extract (RPE) and Rose Receptacle Extract (RRE), ABTS ((2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid))-reducing assay to determine antioxidant activity, and antiaging test with anti-elastase assay. RPE and RRE contained flavonoids, phenols, tannins and alkaloids, but did not contain saponins. RPE contained triterpenoids and terpenoids, while RRE contained steroids, but did not contain terpenoids. The inhibitory concentration (IC50) values in the ABTS reducing assay were 4.46 ± 0.34 μg/mL (RPE) and 15.49 ± 0.23 μg/mL (RRE), while the results of the anti-elastase assay were 17.51 ± 1.47 μg/mL (RPE) and 58.91 ± 2.31 μg/mL (RRE). Both RPE and RRE are potent antioxidant and anti-elastase, and RPE is more active than RRE in these assays.